Ecosystem‐scale carbon allocation among different land uses: implications for carbon stocks in the Yellow River Delta. Issue 5 (1st May 2020) - Li, Yongqiang; Li, Junran; Jiao, Shuying; Li, Ye; Xu, Ziyun; Kong, Baishu
Abstract: The reclamation area of the Chinese Yellow River Delta (YRD) has experienced frequent land use changes in recent decades. The consequence of such land use changes on the stocks and allocation of ecosystem‐scale carbon is not known. Here, we assessed carbon stocks and allocation of four representative land uses in the YRD area: (1) purple alfalfa (LAL), (2) reed and Aeluropus littoralis (RAE), (3) cotton (ECO), and (4) Chinese tamarisk (CTA). The results showed that the overall carbon stocks, and carbon stocks of aboveground, litter, roots, and soil were notably different among different land uses. The native CTA land had the largest overall carbon stock (belowground and aboveground) and had the strongest potential to allocate the carbon to the soil carbon pool (95.72%), followed by the natural grassland (RAE). Alfalfa grassland (LAL) also had a large carbon stock due to its large aboveground biomass, litter, and roots, but the relative allocation proportion of soil carbon stock was lower than that of the other land uses examined. Cotton (ECO) had the lowest soil carbon and total carbon stocks among four land uses. In combining our data on the carbon pool with changes of land use in the YRD area, we argued that land reclamation in the YRD area was likely to turn this area from a carbon sink to carbon source with the release of soil organic carbon. Therefore, cautions should be taken to reduce carbon release, if the reclaimed land be used to plant crops.